Design of Smart Travel Management System Based on Cloud Service. (April 2020) - Gao, Fang; Li, Liangyu
Abstract: The design and implementation of the database is an important task in system development. Many information in the management of smart tourism needs to be saved and managed so that these data can be analyzed later. Therefore, in the process of designing the system, the original number of system requirements is analyzed, and the relationship between business entities is established. Combined with the relational database used by the system, E-R diagram drawing and data table implementation were performed.